Host range expansion of Acinetobacter phage vB_Ab4_Hep4 driven by a spontaneous tail tubular mutation - He, Penggang; Cao, Feng; Qu, Qianyu; Geng, Huaixin; Yang, Xin; Xu, Tong; Wang, Rui; Jia, Xu; Lu, Mao; Zeng, Peibin; Luan, Guangxin (Frontiers in Cellular and Infection Microbiology, 2024)
Acinetobacter baumannii (MDRAB) infections. The application of phages as antibacterial agents is limited by their generally narrow host ranges, so changing or expanding the host ranges of phages is beneficial for phage therapy. Multiple studies have identified that phage tail fiber protein mediates the recognition and binding to the host as receptor binding protein in phage infection. However, the tail tubular-dependent host specificity of phages has not been studied well. In this study, we isolated and characterized a novel lytic phage, vB_Ab4_Hep4, specifically infecting MDRAB strains. Meanwhile, we identified a spontaneous mutant of the phage, vB_Ab4_Hep4-M, which revealed an expanded host range compared to the wild-type phage. A single mutation of G to C was detected in the gene encoding the phage tail tubular protein B and thus resulted in an aspartate to histidine change. We further demonstrated that the host range expansion of the phage mutant is driven by the spontaneous mutation of guanine to cytosine using expressed tail tubular protein B. Moreover, we established that the bacterial capsule is the receptor for phage Abp4 and Abp4-M by identifying mutant genes in phageresistant strains. In conclusion, our study provided a detailed description of phage vB_Ab4_Hep4 and revealed the tail tubular-dependent host specificity in A. baumannii phages, which may provide new insights into extending the host ranges of phages by gene-modifying tail tubular proteins.